2019
DOI: 10.2478/rjim-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide exerts an anti-inflammatory action in obese patients with type 2 diabetes

Abstract: Introduction. Liraglutide (L) is the analogue of human glucagon-like peptide 1 which stimulates glucose-dependent insulin secretion and can modify the level of inflammatory biomarkers. L can influence NF-kB inflammatory cascade, but the mechanisms of anti-inflammatory activities of L remain to be determined. In animal models L influenced an activity of Sirtuin 1(SIRT1). Moreover, recent evidences strongly suggest that SIRT1 up-regulation may serve as a potent therapeutic approach against development and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 28 publications
2
29
1
9
Order By: Relevance
“…In podocyte-specific Sirt1 knockout diabetic nephropathy mouse model, proteinuria increases significantly as compared to diabetic nephropathy mouse ( 41 ). Several studies have demonstrated that SIRT1 plays a positive role via the action of GLP-1 on maintaining glucose homeostasis ( 42 , 43 ). The effect of exenatide on maintaining glucose homeostasis and improving insulin sensibility was attenuated in SIRT1 +/− mice fed with HFD ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In podocyte-specific Sirt1 knockout diabetic nephropathy mouse model, proteinuria increases significantly as compared to diabetic nephropathy mouse ( 41 ). Several studies have demonstrated that SIRT1 plays a positive role via the action of GLP-1 on maintaining glucose homeostasis ( 42 , 43 ). The effect of exenatide on maintaining glucose homeostasis and improving insulin sensibility was attenuated in SIRT1 +/− mice fed with HFD ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exenatide on maintaining glucose homeostasis and improving insulin sensibility was attenuated in SIRT1 +/− mice fed with HFD ( 42 ). Liraglutide exerts a potent anti-inflammatory effect due to the inhibition of NF-κB pathway and upregulated level of SIRT1 in blood samples of patients with obesity and T2DM ( 43 ). Another study showed that SIRT1 and thioredoxin-interacting protein (TXNIP) have opposite effects on oxidative stress and metabolism in mediating the anti-aging interventions ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…12,16,41 Our study showed that LG ameliorated the significant high levels of IL-6 and TNF-α produced from obese ADSCs suggesting the association of anti-inflammatory effects with its anti-proliferative efficacy in obese conditions. Recent studies proved the potent anti-inflammatory effect of LG in obese diabetic patients 37 and in obesity-related glomerulopathy 43 via down-regulation of pro-inflammatory factors including TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…35 LG causes both upregulation of adiponectin and anti-inflammatory effect in diabetic patients. 36,37 Although the anti-proliferative activity of LG has been reported on human prostate 31 and pancreatic 32 cancers as well as in hepatocellular carcinoma cells, 33 it is unknown whether LG could exert anti-proliferative effects against BC, particularly in obese subjects. According to previously mentioned data, we hypothesize that treatment with LG may mitigate the BC growth in obese subjects and this effect is mediated via modulating the secretion of leptin, adiponectin and inflammatory cytokines from ADSCs and cancer cells…”
Section: Introductionmentioning
confidence: 99%
“…164 Liraglutide had an anti-inflammatory effect due to inhibition of NF-kB pathways, down-regulating TNF-α. 165 In addition, treatment with liraglutide improved adiponectin levels. 166…”
Section: The Possible Effect Of Exercise Lifestyle Interventions and Antidiabetics On The Molecular Background Of Eat Inflammationmentioning
confidence: 99%